Stock Return Predictability and Asset Pricing Models - Avramov, Doron (Review of Financial Studies, 2004)
This article develops an asset allocation framework that incorporates prior beliefs about the extent of stock return predictability explained by asset pricing models. We find that when prior beliefs allow even minor deviations from pricing model implications, the resulting asset allocations depart considerably from and substantially outperform allocations dictated by either the underlying models or the sample evidence on return predictability. Under a wide range of beliefs about model pricing abilities, asset allocations based on conditional models outperform their unconditional counterparts that exclude return predictability. Copyright 2004, Oxford University Press.